Usefulness of Computed Tomographic Perfusion Imaging for Appropriate Diagnosis of Acute Cerebral Vessel Occlusion in Case of Anatomic Variations of the Circle of Willis - Jeyanthan Charles James; Daniel Richter; Laura Tomaske; Ruth Schneider; Carsten Lukas; Felix Kaemmerer; Ralf Gold; Christos Krogias (Neurointervention, 2021)
Mechanical thrombectomy (MT) is an effective treatment in patients with acute ischemic stroke (AIS) due to emergent large-vessel occlusion in the anterior circulation. Occlusion of the anterior cerebral artery (ACA) affects up to 15% of these patients. Here we report a case of an elderly patient with an successful MT of an embolic A2-segment occlussion with the anatomic variation of a triplication. Triplication of ACA is a rare anatomical variation, and the occlusion could have been easily overlooked in case of not performing the CT-perfusion (CTP) sequences. As anatomical variations of the circle of Willis are present in most subjects, CTA alone might be limited in the acute setting, particularly for young residents performing the first view on call. This case highlights the importance of including CTP in the initial CT-diagnostic algorithm in AIS patients who are basically eligible for recanalization therapies, irrespective of inconspicuous initial findings in CTA.